Complex Optical Index of HgTe Nanocrystal Infrared Thin Films and Its Use for Short Wave Infrared Photodiode Design. Issue 10 (5th March 2021) - Rastogi, Prachi; Chu, Audrey; Dang, Tung Huu; Prado, Yoann; Gréboval, Charlie; Qu, Junling; Dabard, Corentin; Khalili, Adrien; Dandeu, Erwan; Fix, Baptiste; Xu, Xiang Zhen; Ithurria, Sandrine; et al.
Abstract: The limited investigation of the optical properties of HgTe nanocrystal (NC) thin films has become a bottleneck for the electromagnetic design of devices. Using broadband ellipsometry, the refractive index ( n ) and the extinction coefficient ( k ) are determined for a series of HgTe NC films relevant to infrared sensing applications. Electromagnetic simulations reveal that the n value of HgTe NC thin films can conveniently be approximated by its mean spectral value n = 2.35 ± 0.15. This complex optical index is then used to design a diode with i) a reduced amount of Hg containing material (thin film < 150 nm) and ii) a thickness of the device better‐matched with the carrier diffusion length. It is demonstrated that introducing an aluminum grating onto the transparent conductive electrode leads to an enhanced absorption while reinforcing the work‐function difference between the two electrodes. Broadband (≈1 µm), non‐polarized, and strong absorption up to 100% is designed. This leads to a responsivity of 0.2 A W −1 and a detectivity of 2 × 10 10 Jones for 2 µm cut‐off wavelength at room‐temperature, while the time response is as short as 110 ns. Abstract : As nanocrystals become used for the design of infrared sensor, the unveiling of their complex optical index is of utmost interest for electromagnetic simulation. The latter is then used to design a strongly absorbing device from thin HgTe nanocrystal film.